Density functional study for crystalline structures and electronic properties of Si1−xSnx binary alloys. (14th July 2016) - Nagae, Yuki; Kurosawa, Masashi; Shibayama, Shigehisa; Araidai, Masaaki; Sakashita, Mitsuo; Nakatsuka, Osamu; Shiraishi, Kenji; Zaima, Shigeaki
Abstract: We have carried out density functional theory (DFT) calculation for Si1− x Sn x alloy and investigated the effect of the displacement of Si and Sn atoms with strain relaxation on the lattice constant and E – k dispersion. We calculated the formation probabilities for all atomic configurations of Si1− x Sn x according to the Boltzmann distribution. The average lattice constant and E – k dispersion were weighted by the formation probability of each configuration of Si1− x Sn x . We estimated the displacement of Si and Sn atoms from the initial tetrahedral site in the Si1− x Sn x unit cell considering structural relaxation under hydrostatic pressure, and we found that the breaking of the degenerated electronic levels of the valence band edge could be caused by the breaking of the tetrahedral symmetry. We also calculated the E – k dispersion of the Si1− x Sn x alloy by the DFT+ U method and found that a Sn content above 50% would be required for the indirect–direct transition.